Toward a K-20 Student Unit Record Data System for California - Vernez, Georges (RAND Corporation, 2008)
To improve the progression of students through the educational system and to improve education quality, California needs a robust data system that can track an individual student's progress from kindergarten to college and beyond. The authors review California's multiple existing student data systems and identify steps that could be taken toward building and maintaining an integrated student data system for the state.